Using Index of Compaction in interpreting the distribution and shapes of soil map units of Lower Diyala project.: Using Index of Compaction in interpreting the distribution and shapes of soil map units of Lower Diyala project. (Journal of the College of Education for Women, 2019)
AbstractThis study was conducted by using soil map of LD7 project to interpret thedistribution and shapes of map units by using the index of compaction as anindex of map unit shape explanation. Where there were wide and variedranges of compaction index of map units, where the maximum value was0.892 for MF9 map unit and the lower value was 0.010 for same map unit.MF9 has wide range appearance of index of compaction after those indiceswere statistically analyzed by using cluster analysis to group the similarranges together to ease using their values, so the unit MF9 was considered askey map unit that appears in the soils of LD7 project which may be used toexpect another map units existence in area of that project and areas aroundwhich is considered an important step in soil survey works then classificationand management of soils there. 78.57% of these indices where 0.526 or lessthat means they are low and reflects unit shape that is not simple and almostbeing elongated and branched ones. While 21.42% of these samples were0.526 or more which show high and medium indices with shapes simple ormoderately simple and may have no branches.